John Puller : No Man's Land - Book 4 - Baldacci, David; Brewer, Kyf.; Cassidy, Orlagh (New York : Hachette Audio, 2016)
John Puller may be the US Army's most tenacious investigator, but he's not equipped to face the truth about his mother's disappearance thirty years ago. New evidence has come to light suggesting that Puller's father--a highly decorated Army veteran--may have murdered his wife. When Puller's friend, intelligence operative Veronica Knox, arrives on the scene, he realizes that there's far more to this case than he first thought. He knows that nothing will prevent him from discovering what really happened to his mother--even proving that his father is a killer.
Keywords: United States -- Army Criminal Investigation Command -- Fiction; Cold cases (Criminal investigation) -- Fiction; Murder -- Fiction -- Investigation; Parolees -- Fiction; Detective and mystery fiction; Audiobooks